Effect of storage time of extended-pour and conventional alginate impressions on dimensional accuracy of casts. - Ahmad Rohanian; Ghasem Ommati Shabestari; Somayeh Zeighami; Mohammad Javad Samadi; Ahmad Reza Shamshiri (Tehran University of Medical Sciences, 2014)
Some manufacturers claim to have produced new irreversible hydro-colloids that are able to maintain their dimensional stability during storage. The present study evaluated the effect of storage time on dimensional stability of three alginates: Hydrogum 5, Tropicalgin and Alginoplast.In this experimental in-vitro trial, a total of 90 alginate impressions were made from a Dentoform model using Hydrogum 5, Tropicalgin and Alginoplast alginates. The impressions were stored in a sealed plastic bag without a damp paper towel for 0, 24, 48, 72 and 120 hours and then poured with type III dental stone. Cross-arch (facial of 6 to facial of 6 on the opposite side) and antero-posterior (distal of right first molar to the ipsilateral central incisor) measurements were made with a digital caliper on the casts. Data were analyzed by two-way and one-way ANOVA and Tukey's post-hoc test (P